GEOCHEMISTRY AND ORIGIN OF FERRUGINOUS NODULES IN WEATHERED GRANODIORITIC GNEISSES, MYSORE PLATEAU, SOUTHERN INDIA - Tripathi J.K.; Rajamani V. (My University, 2007)
Fe-nodules occur within saprolites formed from weathering of granodioritic gneisses in the rain-shadow region of the Mysore Plateau adjacent to the Sahyadri Mountains in Southern India. These nodules and their host saprolites were studied for their geochemistry, including chemical speciation, to understand nodule formation and chemical redistribution processes during rock weathering. From their mode of occurrence, and mineralogical and geochemical data, we infer that the nodules originated by a two-stage process in which the initial extensive weathering of gneisses likely facilitated subsequent ferrolysis weathering and nodule formation. Nodules originated by precipitation of goethite, hematite and gibbsite along with several amorphous phases within the matrix of weathered gneisses. This is possible only under hydromorphic conditions, suggesting that parts of the plateau must have gone through a humid phase prior to the present aridity. In the saprolites, Al, Fe, and Ti become enriched because of the removal of Si, Ca, Na, and K. However within the nodule, Fe, Ti, Cr, and Ni are deposited after their chemical transport from the saprolite. Titanium, known for its immobile nature, was also mobilized and concentrated under the conditions of nodule formation. The most important elements in the nodule constitution are Fe, Al, Ti, and Mn, each having both crystalline and amorphous phases. Fe-Ti and Mn oxyhydroxides grain coatings in the saprolites and discrete amorphous Mn and Ti phases in the nodules seem to have scavenged trace elements from the weathering profile. REE were mobilized during weathering and nodule genesis in which Ce and Ti show a strong geochemical coherence. The enrichment of only HREE in saprolite, and both HREE and LREE with significant Ce in the nodule, indicate the control of evolving secondary minerals in the REE redistribution during rock weathering. Strong enrichment of Ce in the weathering profile and in nodules has important implications to the REE chemistry of river waters. © 2007 Elsevier Ltd. All rights reserved.